Aplikasi enkapsulan hydroxy propyl methyl cellulose dan gum arab pada pembuatan bubuk semangka - Ignasius Radix AP Jati; Nicolas Hadisaputra; Erni Setijawaty; Rachel Meiliawati Yoshari (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Watermelon is a widely produced fruit in Indonesia. Abundant production and limited utilization make watermelons susceptible to quality loss and damage. Watermelon can be processed into powder to expand the variety of processing and reduce post-harvest losses. Various drying methods can be carried out, while a cabinet dryer at a temperature of 60-65 °C for 6 hours is considered the simplest method. Moreover, encapsulants such as hydroxy propyl methyl cellulose (HPMC) and gum arabic can be added. This study aims to apply different encapsulants in the watermelon powder manufacturing process and evaluate their effect on the physicochemical properties of the watermelon powder. A nested factorial randomized block design was used. The nest factor is the type of encapsulant, while the concentration is the nesting factor. The difference in concentration was 2.5 %, 5 % and 7.5 % for both HPMC and gum arabic. Each treatment was repeated four times. Watermelon powder quality parameters evaluated were moisture content, hygroscopicity, total phenol, antioxidant activity, color, and pH. ANOVA with = 5 % was implemented for statistical analysis and continued with Duncan's Multiple Range Test if a significant difference was observed. The increasing concentration of gum arabic increased the water content (2.19-3.42 %). While hygroscopicity decreased (21.84-17.33 %), total phenol decreased from 1370.91 to 765.23 mg GAE/kg sample. The antioxidant activity of the sample using the DPPH method was decreased (89.29-52.90 %). The use of gum arabic can maintain the red color of powder and the pH in the range of 5.39-5.57. On the other hand, HPMC application can reduce water content (3.32-2.15 %), hygroscopicity level 23.53-17.17 %; total phenol 1172.05-539.09 mg GAE/kg; antioxidant activity 65.88-29.54 %. The HPMC can maintain the red color of powder and increase the pH (5.83-6.30).